Evaluasi nilai kecernaan in vitro bahan kering dan bahan organik biskuit biosuplemen daun katuk (Sauropus androgynus L.Merr) untuk sapi perah PFH (Faculty of Animal Science, Universitas Brawijaya, 2018)
The aim of this research is to evaluate dry matter digestibility value and organic matter biscuits biosuplemen leaf katuk in vitro. The research materials were biosupplement biscuits, consist of katuk leaf, molasses and concentrate of lactation. The design used was complete randomized design (RAL) with 5 treatments and 3 replications. P1: 10% leaf katuk, 90% concentrate; P2: 20% katuk leaves, 80% concentrate; P3: 30% katuk leaves, 70% concentrate; P4: 40% katuk leaves, 60% concentrate; P5: 50% leaf katuk, 50% concentrate. The variables observed were dry matter digestibility and organic matter. Data were analyzed by using ANOVA. The results showed that the digestibility of dry matter and organic matter in vitro biscuits biosuplemen katuk respectively are 62.39% -72.80% and 58.80% -70.00%. The dry matter digestibility value and the organic matter in vitro for each formulation treatment were not significantly different (P> 0.05). The conclusion of this research is that biosupplement biscuits of katuk leaves has not been able to improve the digestibility of dry matter and organic matter in vitro.